APPADDEKKO DALAM TRADISI PESTA PANEN DI DESA PARANG BADDO KEC. POLONGBANGKENG UTARA KAB. TAKALAR (Studi Unsur-unsur Kebudayaan Islami): Studi Unsur-unsur Kebudayaan Islami - St Nurbaya Kadir (STAI YAPIS Takalar, 2022)
This research took place for 2 months, from April to mid-May this year, using qualitative research methods. The author describes the process of the Appaddekko tradition using a descriptive approach and aims to explore Islamic values in the customs contained in the traditions of the Appaddekko, the tradition of harvesting parties in Parang Baddo Village, Kec. North Polongbangkeng Kab. Takalar. The results showed that the Appaddekko tradition at the harvest party in Parang Baddo Village has Islamic values, namely (1) Religious Values which are manifest as a belief system, and ideas about God, gods, spirits, hell and heaven. (2) Art values such as dance, theater, and music. (3) Social values such as togetherness, friendship, and mutual cooperation. As well as increasing kinship, cohesiveness and a sense of solidarity between communities in Parang Baddo Village.